Plan de renovación y recuperación de la zona portuaria canal auyama para la reactivación económica 2030 - centro educativo para la protección del río Magdalena (2017)
The port of Barranquilla is located 22 kilometers from the mouth of the river Magdalena, which allows a wider connection with the rest of the world and the interior of the country. Known as the golden gate of Colombia thanks to its history. Because of the importance it had to its beginnings. This port has declined over the years, due to various factors such as poor management, that the canal is not so navigable, due to the high degree of pollution that the Magdalena River has, which has been a strategic river for the Competitiveness of the country, since it is the main fluvial connector that connects the north of the country with the central part. Being one of the most important problems, pollution of the Magdalena river.